Effect of space allowance and transport container height on the welfare of fattening rabbits under different environmental thermal conditions - Contreras-Jodar, A.; Dalmau, A.; Bagaria, M.; Barbosa-Filho, J. A. D.; Rendon, M.; Salama, A. A. K.; Velarde, A. (Frontiers in Veterinary Science, 2025)
This study evaluated the combined effects of container space allowance, height, and ambient thermal conditions on the welfare of fattening rabbits during simulated transport. Nine hundred rabbits were exposed to three space allowances (121, 150, and 191 cm2/kg; S121, S150, S191), two container heights (20 and 35 cm; H20, H35), and four thermal environments (21.4 °C, 25.9 °C, 30.0 °C, and 33.5 °C, T1–T4, all at 50–68% RH) for 8 h after 6-h fasting. Welfare was assessed via thermophysiological (rectal temperature, RT; body weight loss, BWL) and metabolic indicators (hematocrit, glucose, LDH, corticosterone, creatine kinase, NEFAs). Thermographic imaging of ear and lacrimal regions was correlated with RT to validate a non-invasive method for assessing thermal stress. T4 was stopped after 5 h due to severe compromise in S121 and S150, especially in H35. T1 increased hypothermia risk compared to T2 and T3 (p = 0.043). S191 increased hypothermia risk compared to S150 and S121. Cage height did not affect hypothermia (p = 0.875) but increased hyperthermia risk under T3, especially in S150 and S121 (p < 0.037). BWL varied with thermal state (p < 0.001): 54.4 g in hypothermia, 65.2 g in normothermia, 74.1 g in hyperthermia. RT correlated with lacrimal (r = 0.743) and ear (r = 0.704) temperatures (p < 0.001). Hematocrit, LDH, and creatine kinase remained stable. Glucose varied with space allowance (p = 0.002) and tended to vary with height (p = 0.070), highest in S121 and H20. NEFAs decreased under T3 (p < 0.010) and tended to under T2. These findings highlight the importance of optimizing transport conditions and support thermography as a welfare monitoring tool.